Icosahedral metallacarborane/carborane species derived from 1, 1′-bis(o-carborane)12. Issue 12 (23rd February 2015) - Thiripuranathar, Gobika; Man, Wing Y.; Palmero, Cesar; Chan, Antony P. Y.; Leube, Bernhard T.; Ellis, David; McKay, David; Macgregor, Stuart A.; Jourdan, Laure; Rosair, Georgina M.; Welch, Alan J.
Abstract : Both unisomerised and isomerised singly-metallated derivatives of 1, 1′-bis( o -carborane) with both {Ru(arene)} and (CoCp} fragments have been prepared and characterised. Abstract : Examples of singly-metallated derivatives of 1, 1′-bis( o -carborane) have been prepared and spectroscopically and structurally characterised. Metallation of [7-(1′-1′, 2′- closo -C2 B10 H11 )-7, 8- nido -C2 B9 H10 ] 2− with a {Ru( p -cymene)} 2+ fragment affords both the unisomerised species [1-(1′-1′, 2′- closo -C2 B10 H11 )-3-( p -cymene)-3, 1, 2- closo -RuC2 B9 H10 ] (2 ) and the isomerised [8-(1′-1′, 2′- closo -C2 B10 H11 )-2-( p -cymene)-2, 1, 8- closo -RuC2 B9 H10 ] (3 ), and2 is easily transformed into3 with mild heating. Metallation with a preformed CoCp 2+ fragment also affords a 3, 1, 2-MC2 B9 -1′, 2′-C2 B10 product [1-(1′-1′, 2′- closo -C2 B10 H11 )-3-Cp-3, 1, 2- closo -CoC2 B9 H10 ] (4 ), but if CoCl2 /NaCp is used followed by oxidation the result is the 2, 1, 8-CoC2 B9 -1′, 2′-C2 B10 species [8-(1′-1′, 2′- closo -C2 B10 H11 )-2-Cp-2, 1, 8- closo -CoC2 B9 H10 ] (5 ). Compound4 does not convert into5 in refluxing toluene, but does do so if it is reduced and then reoxidised, perhaps highlighting the importance of the basicity of the metal fragment in the isomerisation of metallacarboranes. A computational study of 1, 1′-bis( o -carborane) is in excellent agreement with a recently-determined precise crystallographic study and establishes that the {1′, 2′- closo -C2 B10 H11 } fragment is electron-withdrawing compared to H.